Lixisenatide requires a functional gut-vagus nerve-brain axis to trigger insulin secretion in controls and type 2 diabetic mice - Charpentier, Julie; Waget, Aurélie; Klopp, Pascale; Magnan, Christophe; Cruciani-Guglielmacci, Céline; Lee, Shin Jae; Burcelin, Rémy; Grasset, Estelle (American journal of physiology: Gastrointestinal and liver physiology, 2018)
Endogenous glucagon-like peptide-1 (GLP-1) regulates glucose-induced insulin secretion through both direct β-cell-dependent and indirect gut-brain axis-dependent pathways. However, little is known about the mode of action of the GLP-1 receptor agonist lixisenatide. We studied the effects of lixisenatide (intraperitoneal injection) on insulin secretion, gastric emptying, vagus nerve activity, and brain c-Fos activation in naive, chronically vagotomized, GLP-1 receptor knockout (KO), high-fat diet-fed diabetic mice, or db/db mice. Lixisenatide dose-dependently increased oral glucose-induced insulin secretion that is correlated with a decrease of glycemia. In addition, lixisenatide inhibited gastric emptying. These effects of lixisenatide were abolished in vagotomized mice, characterized by a delay of gastric emptying and in GLP-1 receptor KO mice. Intraperitoneal administration of lixisenatide also increased the vagus nerve firing rate and the number of c-Fos-labeled neurons in the nucleus tractus solitarius (NTS) of the brainstem. In diabetic mouse models, lixisenatide increased the firing rate of the vagus nerve when administrated simultaneously to an intraduodenal glucose. It increased also insulin secretion and c-Fos activation in the NTS. Altogether, our findings show that lixisenatide requires a functional vagus nerve and neuronal gut-brain-islets axis as well as the GLP-1 receptor to regulate glucose-induced insulin secretion in healthy and diabetic mice. NEW & NOTEWORTHY Lixisenatide is an agonist of the glucagon-like protein (GLP)-1 receptor, modified from exendin 4, used to treat type 2 diabetic patients. However, whereas the mode of action of endogenous GLP-1 is extensively studied, the mode of action of the GLP-1 analog lixisenatide is poorly understood. Here, we demonstrated that lixisenatide activates the vagus nerve and recruits the gut-brain axis through the GLP-1 receptor to decrease gastric emptying and stimulate insulin secretion to improve glycemia.